Lake Sediment Methane Responses to Organic Matter are Related to Microbial Community Composition in Experimental Microcosms - Bertolet, Brittni L.; Koepfli, Cristian; Jones, Stuart E. (Frontiers in Environmental Science, 2022)
Lake sediment microbial communities mediate carbon diagenesis. However, microbial community composition is variable across lakes, and it is still uncertain how variation in community composition influences sediment responses to environmental change. Sediment methane (CH4) production has been shown to be substantially elevated by increased lake primary productivity and organic matter supply. However, the magnitude of the response of CH4 production varies across lakes, and recent studies suggest a role for the microbial community in mediating this response. Here, we conducted sediment incubation experiments across 22 lakes to determine whether variation in sediment microbial community composition is related to the response of sediment CH4 production to increases in organic matter. We sampled the 22 lakes across a gradient of pH in order to investigate lakes with variable sediment microbial communities. We manipulated the incubations with additions of dried algal biomass and show that variation in the response of CH4 production to changes in organic matter supply is significantly correlated with metrics of sediment microbial community composition. Specifically, the diversity and richness of the non-methanogen community was most predictive of sediment CH4 responses to organic matter additions. Additionally, neither metrics of microbial abundance nor preexisting organic matter availability explained meaningful variation in the response. Thus, our results provide experimental support that differences is sediment microbial communities influences CH4 production responses to changes in organic matter availability.